(untitled) (Bangladesh Journal of Medicine, 2024)
Introduction: Human immunodeficiency virus (HIV) was discovered in 1983, while acquired immunodeficiency syndrome (AIDS) was first detected in 1981. Since then, it continues to be a public health problem. The phenomenon of HIV/AIDS is best viewed as a pandemic affecting almost all countries of the world. The first case of HIV/AIDS in Bangladesh was documented in 1989.This study was conducted to evaluate the baseline haematologicalcharacteristic in individuals prior to initiating antiretroviral therapy for HIV. Methods: This study was a cross sectional analytical study conducted among one hundred and fifty-four HIV positive patients attending at ART center, Bangabandhu Sheikh Mujib Medical University. Patients were included as per inclusion and exclusion criteria. Co-morbid conditions were excluded mostly by self-reporting and clinically relevant investigations. Result:The study revealed that HIV infected patients were predominantly middle-aged and young comprising > 70% of the patients with the mean age of the patients being 35.5 ± 9.5 years (range: 20-60 years). A male preponderance was observed in the study with a male-to-female ratio being 3:1. The majority (92.2%) of patients received first-line ART. The red cell indices like Hct, MCV, MCH, and MCHC were also low at the initiation of therapy but changed to normality after treatment. Conclusion: From the findings of the study, it can be concluded that HIV infected individuals are predominantly male, middle-aged, and young. The most common haematological abnormality is anaemia which is significantly reduced in percentage after a mean treatment period of nine and a half months with ART. Bangladesh J Medicine 2024; 35(1): 26-32